2009
DOI: 10.1590/s1413-70542009000700061
|View full text |Cite
|
Sign up to set email alerts
|

Teores do óleo essencial de cidrão [Aloysia triphylla (L'Hérit) Britton (Verbenaceae)] em diferentes horários de colheita e processamentos pós-colheita

Abstract: RESUMOEste estudo foi realizado com o objetivo de avaliar o teor do óleo essencial de cidrão [Aloysia triphylla (L´Hérit) Britton] em diferentes horários de colheita e processamentos pós-colheita. O delineamento utilizado foi inteiramente casualizado. As colheitas foram realizadas em três horários distintos (8 h, 12 h e 16 h), com três repetições. Os processamentos pós-colheita foram cinco: T1-folhas frescas fragmentadas em 1cm; T2-folhas frescas processadas em liquidificador; T3-folhas frescas inteiras; T4-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
2
3
0
2
Order By: Relevance
“…A total of 17 and 16 compounds were identified in the essential oil of the guava leaves collected during the rainy and dry seasons, respectively. Similar results were reported by Craveiro et al (1981) in their study on the chemical composition of the essential oil of the guava leaves. RI* Retention index obtained with reference to the n-alkane homologous series using an SPB-5 column.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…A total of 17 and 16 compounds were identified in the essential oil of the guava leaves collected during the rainy and dry seasons, respectively. Similar results were reported by Craveiro et al (1981) in their study on the chemical composition of the essential oil of the guava leaves. RI* Retention index obtained with reference to the n-alkane homologous series using an SPB-5 column.…”
supporting
confidence: 90%
“…The higher essential oil content observed during the rainy season than that during the dry season can be attributed to the climactic conditions. The average temperature (29 °C) and relative humidity (70%) were relatively high in January offering favorable conditions for the production of essential oil (BRANT et al, 2008). Further, the long summer days might have been an influencing factor, as well, offering conditions conducive for the vegetative growth of the plants.…”
mentioning
confidence: 99%
“…O adensamento de plantas alterou a composição qualitativa e quantitativa do óleo essencial, resultando em menores teores de geranial, neral e limoneno (Tabela 3). Brant et al (2009) encontraram teores semelhantes de neral (20%) e geranial (30%), em plantas de Aloysia triphylla, cultivadas no espaçamento de 1,0 x 1,0 m. Nas análises de Brant et al (2009), o citral (geranial + neral) correspondeu a, aproximadamente, 50% do óleo essencial. Já, neste trabalho, o teor de citral foi de 64,45%, no espaçamento de 1,0 x 1,0 m.…”
Section: Resultsunclassified
“…These factors contributed to the overlapping of curves for the spring and summer seasons, especially from 60 DABS. In the same context, Brant et al (2008) found slow growing Aloysia triphylla plants and reducing the essential oil content due to the presence of adverse weather conditions (rainfall, humidity and temperature).…”
Section: Leaf Area Of Aloysia Triphylla Is Altered By Shading Levelsmentioning
confidence: 91%